Keterampilan Berpikir Analisis Calon Guru IPA melalui Model 4A (Analisis Fenomena, Analisis Informasi, Analisis Data, Analisis Temuan) - Septi Budi Sartika; Nur Efendi; Luluk Iffatur Rocmah (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2020)
The analytical thinking skills is important are mastered in all areas of the work, so it needs to be trained at school. But in fact, only 5% of Indonesian students have analytical competence, the competency of most students at the level of knowledge or memorization. Research is conducted to uncover activities, analytical thinking skills, and pre-service student teachers' of natural science education responses through model 4A (phenomenon Analysis, information Analysis, data Analysis, and findings Analysis). The results of study were obtained that: 1) pre-service student teachers' activities are still relevant to learning; 2) the results of the average test results analytical thinking skills, it can be said high that is 78.9; and 3) pre-service student teachers' response to the fluid lecture with model 4A is categorized positively. These results, need to be encouraged to other courses so that the possibility of analytical thinking skills will increase significantly.